The Effect of Leachate Waters on the Quality of Free Groundwater in Air Dingin Landfill, Padang City - Alamsyah, Takdir; Barlian, Eri; Syah, Nurhasan (Sumatra Journal of Disaster, Geography and Geography Education, 2019)
The purpose of this study is 1) to know the condition of physical parameters, free groundwater chemistry; 2) to what extent of leachate water contamination of against free groundwater in the Air Dingin landfill, Padang City. The data analysis technique used in this study is based on Minister of Health Regulation Number 419/1990 concerning Water Quality Requirements and Supervision, and Government Regulation Number 82/2010 concerning Management of Water Quality and Water Pollution Control. The water quality physics test results show 1) smell and taste meet the quality standard requirements; 2) water temperature meets quality standard requirements; 3) watercolour meets quality standard requirements; 4) Dissolved Solids (TDS) meet the quality standard requirements; and 5) Suspended Solids (TSS) meet the quality standard requirements, while the chemical quality of water shows 1) pH below the quality standard; 2) Arsenic below the quality standard; 3) Cadmium is below the quality standard; 4) Chromium below the quality standard; 5) Iron below the quality standard; 6) Lead below the quality standard; 7) Manganese below the quality standard; 8) Free groundwater below the quality standard; and 9) COD below the quality standard.. Leachate water that comes out laterally from the garbage pile tends to flow following the contour of the land towards a lower direction.